Treatment of vitiligo with autologous epidermal transplantation using the roof of suction blisters, first in Bangladesh - Khondoker, MS; Rabbi, SMR; Awwal, R; Hussain, DAS (Journal of Dhaka Medical College, 2010)
Corrigendum There is correction in the Journal of Dhaka Medical College, April 2009 issue (Vol. 18, No. 1). In the original article titled "Treatment of vitiligo with autologous epidermal transplantation using the roof of suction blisters, first in Bangladesh", the name of the first author will have to be read Khondoker MS instead of Khundkar SH, and in address of correspondence Dr. Md. Sajjad Khondoker instead of Prof. Shafquat Hussain Khundkar at page no. 58. On 15/02/2011, the first author's name was changed from SH Khundkar to MS Khondoker on the online edition of the journal on BanglaJOL. We report our experience of autologous epidermal transplantation for 30 (Thirty) patients with vitiligo. The vitiligo in 25 (Twenty five) patients was stable whereas in the rest (5) it was active. Autologous epidermal transplantation was performed using suction blister roofs from normal pigmented skin to vitiligo skin that was failed to repigment using topical steroid and/or psoralenultraviolet- A treatment. Grafts were well taken in all the patients. Only three of them are presented as case report in this article. There were no complications except mild hyper pigmentation at the donor areas. For the patient who had active vitiligo, depigmentation of the graft and concomitant Koebner‘s phenomenon at the donor site were observed 3 weeks after the procedure. We conclude that autologous epidermal transplantation using the roof of suction blisters is an excellent and safe regimenting procedure for stable, localized vitiligo and the active disease precludes transplantation. Key words: Epidermis surgery; vitiligo therapy; transplantation alutologous. DOI: 10.3329/jdmc.v18i1.6308 J Dhaka Med Coll. 2009; 18(1) : 58-63